The Prospects for Higher Education - Southern Newspaper Publishers Association, Atlanta, GA.; Hobbs, Nicholas; Southern Newspaper Publishers Association, Atlanta, GA. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1971)
The Southern Newspaper Publishers Association (SNPA) Foundation, in cooperation with various Southern universities, each year conducts a program of seminars for Southern journalists. The purpose of the seminars is to give those whose responsibility it is to report, edit, and comment on the news the opportunity to increase their knowledge and understanding of the complex events with which they deal in their work. The 1971 seminar, held at Vanderbilt University, dealt with the future prospects for higher education. This document is comprised of papers presented at that seminar. The papers are: (1) "University and Society: Educational Freedom and Institutional Obligation"; (2) "Financing Higher Education in the 'Crisis' Period"; (3) "A Challenge to Higher Education"; (4)"Educational Reform and Social Change: A Student Perspective"; (5) "The Higher Education of Black Americans for the Decade of the 1970s"; (6) "The Governance of Universities"; and (7) "The Community College: Myth and Reality". (HS)
Availability: Southern Newspaper Publishers Association Foundation, P.O. Box 11606, Atlanta, Georgia 30305 ($2.00).
Educational level discussed: Higher Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Accountability; Black Education; Community Colleges; Educational Change; Educational Finance; Educational Innovation; Educational Planning; Governance; Higher Education; Journalism